Exploring Enablers and Barriers of M-Banking Adoption for Financial Inclusion in Rural India - Raju, Gosala; Gupta, Shradha (Indian Journal of Finance, 2026)
Purpose : The objective of this research was to explore critical determinants of mobile banking (M-banking) adoption for achieving financial inclusion in rural India. Design/Methodology/Approach : An integrated research model was assessed through a two-step CB-SEM to explore the key determinants of M-banking adoption. A total of 404 data samples were collected from Andhra Pradesh (130), Karnataka (140), and Telangana (134). Findings : The results established a positive impact of usefulness, ease of use, self-efficacy, and social influence on M-banking adoption, and a negative impact of cost and risk on M-banking adoption. Self-efficacy had a positive impact on usefulness and ease of use; whereas, social influence had a negative impact on risk. Practical Implications : The study contributed to technology and behavioral research. Furthermore, it provides a better understanding of key factors of M-banking adoption among rural populations. Originality : This study used a unique research model that integrated the critical variables of TAM, UTAUT, DOI, and TPB. The research model explained 79.4% of the variation in m-banking adoption.